The Students’ Perception on Online Learning Through Whatsapp During Covid-19 Pandemic at SMA Negeri 1 Tejakula - Arnaya, Ida Bagus Putu Adhitya; Padmadewi, Ni Nyoman; Dewi, Ni Luh Putu Eka Sulistia (Jurnal Penelitian Mahasiswa Indonesia, 2024)
This study aims to investigate the student perception of online learning through whatsapp during pandemic at SMA NEGERI 1 TEJAKULA. The research using qualitative method and utilizing questionnaire and interview guides for collecting the data. The study using 107 student from 3 classes from the same grades, namely XII 1, 2, and 3 Bahasa. The researcher used four closed-ended question for the questionnaire, which distributed to three XII Bahasa classes and for the interview guide the researcher using six open-ended question were conducted to there student in Indonesian language to avoid misunderstanding and language gap. The dimension of usefulness (questionnaire) and ease of use (interview guide) were adapted from Venkatesh and Altawaty to measure perceptions. The result showing that the student experienced the improvement on grammar and vocabulary, the student feel helped in learning process, achieveing best learning outcomes, and the student feel flexible and practical iin using online learning through whatsapp during pandemic, however, despite of the statement before, the student having an issue namely internet connectivity and the enjoyment on online learning through whatsapp during the pandemic. The study was carry out by the researcher that expected to be a reference and relfection for teacher also for further to enhance and develop online learning through whatsapp, especially in providing a stable internet connection in order to facilitate the student’s comfortable in participating online learning through whatsapp, and also creating and giving the student a conducive teaching atmosphere and method, thus the student enjoying the online learning process through whatsapp.